Precious but convenient means of prevention and treatment: physiological molecular mechanisms of interaction between exercise and motor factors and Alzheimer’s disease - Hao, Zikang; Liu, Kerui; Zhou, Lu; Chen, Ping (Frontiers in Physiology, 2023)
Disproportionate to the severity of Alzheimer's disease (AD) and the huge number of patients, the exact treatment and prevention of AD is still being explored. With increasing ageing, the search for means to prevent and treat AD has become a high priority. In the search for AD, it has been suggested that exercise may be one of the more effective and less costly means of preventing and treating AD, and therefore a large part of current research is aimed at exploring the effectiveness of exercise in the prevention and treatment of AD. However, due to the complexity of the specific pathogenesis of AD, there are multiple hypotheses and potential mechanisms for exercise interventions in AD that need to be explored. This review therefore specifically summarises the hypotheses of the interaction between exercise and AD from a molecular perspective, based on the available evidence from animal models or human experiments, and explores them categorised according to the pathologies associated with AD: exercise can activate a number of signalling pathways inhibited by AD (e.g. Wnt and PI3K/Akt signalling pathways) and reactivate the effects of downstream factors regulated by these signalling pathways, thus acting to alleviate autophagic dysfunction, relieve neuroinflammation and mitigate Aβ deposition. In addition, this paper introduces a new approach to regulate the blood-brain barrier, i.e. to restore the stability of the blood-brain barrier, reduce abnormal phosphorylation of tau proteins and reduce neuronal apoptosis. In addition, this paper introduces a new concept." Motor factors" or "Exerkines", which act on AD through autocrine, paracrine or endocrine stimulation in response to movement. In this process, we believe there may be great potential for research in three areas: (1) the alleviation of AD through movement in the brain-gut axis (2) the prevention and treatment of AD by movement combined with polyphenols (3) the continued exploration of movement-mediated activation of the Wnt signalling pathway and AD.